Impact of microfinance on poverty: qualitative analysis for Grameen Bank borrowers - Mohammad, Aslam; Kumar, Senthil; Sorooshian, Shahryar (Sciedu Press, 2019)
Poverty is economic, social, political and even moral issue all over the world. Microfinance has been designed to eliminate poverty and may help marginal people to materialize their dreams. Microfinance has been formalized primarily in Bangladesh with this concept. Grameen Bank (GB) has been serving large number of people below poverty level here. Initially, microfinance institutions have been supported by the Government or Donor assuming its positive impact on borrowers. However, ambiguous impacts have been reported in several studies that make microfinance questionable. Therefore, this study intent to measure the impact of microfinance on GB borrowers through the process of qualitative changes in borrowers lives. The process has been measured by some case studies for participant and non participant borrowers using Modified Household Economic Portfolio Model (M HEPM). Our qualitative analysis shows that microfinance makes positive changes in the process of borrowers lives observed through financial and activity diaries of the borrowers.